Econometric analysis of Singapore's export performance in the 1980s - Tan, Tok Seng (2015)
This project aims to explain the growth of Singapore's export volume in the 1980s and determine what are the contributing factors. It has been established by the Monetary Authority of Singapore (MAS), the Singapore's quasi Central Bank, that a strong or weak Singapore dollar will not influence Singapore's long term export competitiveness. This position adopted by MAS is to a certain extent supported by the research findings which revealed that Singapore's real effective exchange rate (REER) does not seem to play an important direct role in export performance. However, the direct influences of foreign demand and unit labour cost (ULC) on export performance are significant. From this simple econometric modelling, it is conclusive to say that Singapore's domestic inflation will erode its export competitiveness. To conclude one step further, as Singapore is a small and open economy with high dependence on imports, it is not presumptuous to say that a strong Singapore dollar will actually contribute to long term export competitiveness by mitigating the negative effects of imported inflation into Singapore. The other significant factor is foreign demand. Singapore has a small domestic market which implies a high reliance on foreign markets for its exports. Therefore, a strong world economic growth would increase demand for its exports and weak economic growth overseas could reduce the foreign demand. Thus, the research findings revealed both internal and external factors that strongly explain Singapore's export growth in the 1980s. The implications from this result are two-fold.As Singapore is highly dependent on world demand for its exports. its commitment to free trade subjects the economy to the dictates of events beyond its control. which can at times be detrimental. Therefore. it must be willing and able to make internal adjustments as required by changes in external circumstances in order to maximize the benefits from free trade. It also has to be quick in capitalizing opportunities and yet flexible enough to alter directions in the face of adversity. The other implication is very much in Singapore's control. The MAS policy with regard to Singapore's exchange rate had worked in the 1980s. The strictest control over imported inflation had to be exercised (See Appendix A). This control. coupled with an effective management of Singapore's labour cost and other costs of doing business. ensure its long term export competitiveness. Thus. it implies that domestic price stability will and should continue to be the cornerstone in the total management of Singapore's external competitiveness.